Brazilin Removes Toxic Alpha-Synuclein and Seeding Competent Assemblies from Parkinson Brain by Altering Conformational Equilibrium. Issue 8 (16th April 2021) - Nahass, George R.; Sun, Yuanzi; Xu, Yong; Batchelor, Mark; Reilly, Madeleine; Benilova, Iryna; Kedia, Niraja; Spehar, Kevin; Sobott, Frank; Sessions, Richard B.; Caughey, Byron; Radford, Sheena E.; et al.
Graphical abstract: Highlights: The natural polyphenol Brazilin binds to monomeric and fibrillar α-syn. Brazilin specifically binds the aggregation-competent compact monomer conformation. Brazilin inactivates seeding-competent α-syn isolated from Parkinson patients' brains. Brazilin detoxifies α-syn aggregation intermediates and stabilizes mature amyloid fibril clusters. Abstract: Alpha-synuclein (α-syn) fibrils, a major constituent of the neurotoxic Lewy Bodies in Parkinson's disease, form via nucleation dependent polymerization and can replicate by a seeding mechanism. Brazilin, a small molecule derived from red cedarwood trees in Brazil, has been shown to inhibit the fibrillogenesis of amyloid-beta (Aβ) and α-syn as well as remodel mature fibrils and reduce cytotoxicity. Here we test the effects of Brazilin on both seeded and unseeded α-syn fibril formation and show that the natural polyphenol inhibits fibrillogenesis of α-syn by a unique mechanism that alters conformational equilibria in two separate points of the assembly mechanism: Brazilin preserves the natively unfolded state of α-syn by specifically binding to the compact conformation of the α-syn monomer. Brazilin also eliminates seeding competence of α-syn assemblies from Parkinson's disease patient brain tissue, and reduces toxicity of pre-formed assemblies in primary neurons by inducing the formation of large fibril clusters. Molecular docking of Brazilin shows the molecule to interact both with unfolded α-syn monomers and with the cross-β sheet structure of α-syn fibrils. Our findings suggest that Brazilin has substantial potential as a neuroprotective and therapeutic agent for Parkinson's disease.